A Review of Recent Progress in the Mechanisms and Effectiveness of Acupuncture for Treating Allergic Rhinitis - Bu F; Lou Z (International Journal of General Medicine)
Fan Bu, Zhengchi Lou The Third Affiliated Hospital of Xinxiang Medical University, Henan, 453000, People’s Republic of ChinaCorrespondence: Zhengchi Lou, Email louzhc1977@163.comAbstract: This review aims to summarize and evaluate the latest clinical evidence and mechanistic studies regarding acupuncture for the treatment of allergic rhinitis AR. Compared with traditional medical treatment, acupuncture treatment of allergic rhinitis has fewer side effects and drug dependence, especially for those patients who do not respond well to medical treatment, acupuncture treatment has become a new hope. By analyzing results from RCTs, systematic reviews, and meta-analyses, the significant effectiveness of acupuncture in improving AR symptoms is clarified. We explore the mechanisms of acupuncture in immune regulation, neural modulation, inflammation modulation, and microbiota modulation, and assess its clinical efficacy and safety. The results indicate that acupuncture significantly alleviates AR symptoms through multiple biological regulatory mechanisms. Future research should further standardize acupuncture treatment protocols and deepen mechanistic studies to optimize its clinical application.Keywords: acupuncture, allergic rhinitis, mechanisms, efficacy